Enzimas termoestáveis: fontes, produção e aplicação industrial - Gomes, Eleni [UNESP]; Guez, Marcelo Andrés Umsza [UNESP]; Martin, Natalia [UNESP]; Silva, Roberto da [UNESP] (Sociedade Brasileira de Química, 2007)
REVIEW: Living organisms encountered in hostile environments that are characterized by extreme temperatures rely on novel molecular mechanisms to enhance the thermal stability of their proteins, nucleic acids, lipids and cell membranes. Proteins isolated from thermophilic organisms usually exhibit higher intrinsic thermal stabilities than their counterparts isolated from mesophilic organisms. Although the molecular basis of protein thermostability is only partially understood, structural studies have suggested that the factors that may contribute to enhance protein thermostability mainly include hydrophobic packing, enhanced secondary structure propensity, helix dipole stabilization, absence of residues sensitive to oxidation or deamination, and increased electrostatic interactions. Thermostable enzymes such as amylases, xylanases and pectinases isolated from thermophilic organisms are potentially of interest in the optimization of industrial processes due to their enhanced stability. In the present review, an attempt is made to delineate the structural factors that increase enzyme thermostability and to document the research results in the production of these enzymes.
Thermostable enzymes: sources, production and industrial applications
Keywords: Thermostable enzyme; thermophilic microorganism; thermal adaptation